Psychological help-seeking intention among health sciences students - Dela Fuente, Evangeline B.
Help-seeking is considered to be a critical school readiness skill. This skill is particularly useful for students even for non-academic problems which may affect academics such as psychological concerns. Psychological help-seeking must be well-developed among students, more so among future health professionals for its utility in their personal and professional lives. Help-seeking intention is an important determinant of help-seeking behavior. While not all students may need to engage in psychological help-seeking behavior, all students must possess the intention to do so if the need should arise. The research objective for the present study is to determine the presence or absence of psychological help-seeking intention and factors which influence it among health science students. A total of 386 health science students from UP Manila participated in the study. The current work is a form of descriptive research which utilized a cross-sectional survey. A student questionnaire was prepared based on existing validated questionnaires to assess the variables of interest: the General Help-Seeking Questionnaire-Vignette version and the Attitudes to Seeking Professional Psychological Help Scale-Short version. Data on possible reasons was gathered through key informant interviews to supplement the discussion of results and was not meant to be exhaustive. Results of the study indicate the presence of help seeking intention in a majority of the participants. Participants were more inclined to seek help for others than for themselves despite knowing that help is needed. Among the factors considered in this study, the results showed that those which may have an influence on Help-Seeking Intention were Year Level, College Course and Type of Problem but not Sex and Living Arrangement. For attitude toward Psychological Help-seeking Attitude toward Psychological Help-seeking, an overall mean of 25.57 indicates a positive attitude toward seeking professional psychological help. Among the factors considered in this study, the results showed that College Course and Type of Problem may have an influence on attitude toward seeking professional psychological help but not Sex, Year Level, and Living Arrangement. The most preferred source of help was friends and classmates, closely followed by parents, relatives/other family member. Formal sources were third in rank, followed by Semi-formal sources and lastly by other options. Recommendations on how to enhance help-seeking intention and attitude to professional psychological help-seeking were discussed. This study constitutes a significant contribution to the research base on psychological help-seeking intention among students in the Philippines in general and health science students in particular. The findings may help students and teachers to become more aware of their own help-seeking intention and may enable school leaders and curriculum planners to identify improvements to the curriculum. It can also provide direction for further research on help-seeking among health science students in the Philippines.